Behind East Asian growth : the political and social foundations of prosperity - Rowen, Henry S. (Routledge, 1998)
A wide-ranging, interdisciplinary analysis of the evolution of successful economic policies in East Asia, this study advances a thorough examination of the sustained economic growth enjoyed by the countries in this region.